The prevalence of unintended pregnancy and its influence on pregnancy experience in Tabriz, Iran, 2023: a cross-sectional study - Mahsa Maghalian; Roghayeh Nikanfar; Mahsan Nabighadim; Mojgan Mirghafourvand (BMC, 2024)
Abstract Background There is a lack of quantitative studies that specifically measure the association between the experience of pregnancy and unintended pregnancy. The present study aims to address the prevalence of unintended pregnancy and identify its predictors. Additionally, the study explores whether unintended pregnancy is associated with pregnancy uplifts and hassles. Methods This cross-sectional study was conducted on 488 pregnant women between 20 to 40 weeks' gestation at the comprehensive health center in Tabriz City from February 2022 to January 2023. A cluster sampling method was used for sampling, and data were collected using socio-demographic questionnaires and the Pregnancy Experience Scale (PES). Descriptive statistics were used to describe the socio-demographic characteristics and the prevalence of unintended pregnancy. Binary logistic regression was employed to identify the predictors of pregnancy desirability. To examine the relationship between unintended pregnancy and pregnancy experience, an independent t-test was used for bivariate analysis, and a general linear model (GLM) was utilized for multivariate analysis, with control for potential confounding variables. Results The prevalence of unintended pregnancies was 30.7% (24.3% unwanted pregnancies, and 6.4% mistimed pregnancies). The results of the binary logistic regression indicated that the lower age of both the woman and her spouse were significant predictors for unintended pregnancy (P < 0.05). Based on an independent t-test, the mean score for uplifts in women with unintended pregnancy was significantly lower than in women with intended pregnancy (mean difference (MD): -4.99; 95% confidence interval (CI): -5.96 to -4.02; p < 0.001), While the mean score of hassles in women with unintended pregnancy was significantly higher than women with intended pregnancy (MD: 2.92; 95% CI: 2.03 to 3.80; p < 0.001). The results of GLM showed that women who had unintended pregnancies had significantly lower scores for uplifts (B = -4.99; 95% CI: -5.96 to -4.03; P < 0.001) and higher scores for hassles (B = 2.92; 95% CI: 2.06 to 3.78; P < 0.001). Conclusions The high prevalence of unintended pregnancies in Tabriz highlights the importance of targeted interventions to address this issue, considering the policy framework and unique challenges faced by women. Future studies should focus on developing context-specific interventions that effectively meet the needs of women with unintended pregnancies.